Handbook of Research on User Interface Design and Evaluation for Mobile Technology 2008
DOI: 10.4018/978-1-59904-871-0.ch038
|View full text |Cite
|
Sign up to set email alerts
|

Designing Mobile Applications to Support Mental Health Interventions

Abstract: The advent of mobile technology has brought computing to a wide range of new contexts, some of which are highly sensitive and place new constraints on the designer. In this chapter we discuss issues related to the design and evaluation of mobile software for sensitive situations where access to the end-user is extremely restricted. We focus on the specific example of technological interventions that support adolescents in mental health care settings. We examine the practical and ethical constraints placed on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 24 publications
1
38
1
1
Order By: Relevance
“…The process is user-centered from the outset involving end users (youth, therapists) participating in multiple iterative rounds of design, testing, redesign, and retesting until the interface is deemed easy to use, acceptable, and ready for implementation [64]. In the area of mental health, ethical guidelines emphasizing the protection of patients against harm [65,66] suggest that, to ensure a safe design, the process should begin outside the context of treatment with end users who are similar to the target patient end users but are free of diagnosed mental health problems. Once the design is deemed safe, further rounds of testing and refinement are conducted with target end users who are diagnosed and in treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process is user-centered from the outset involving end users (youth, therapists) participating in multiple iterative rounds of design, testing, redesign, and retesting until the interface is deemed easy to use, acceptable, and ready for implementation [64]. In the area of mental health, ethical guidelines emphasizing the protection of patients against harm [65,66] suggest that, to ensure a safe design, the process should begin outside the context of treatment with end users who are similar to the target patient end users but are free of diagnosed mental health problems. Once the design is deemed safe, further rounds of testing and refinement are conducted with target end users who are diagnosed and in treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The think aloud method [65] involves verbalizing thoughts while performing a task. It is effective for usability testing because it helps identify which interface features users find intuitive and easy to use and which require improvement and further evaluation [65].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer trials have been used at a later stage of development to help evaluate the suitability, viability and appeal of systems in realistic contexts (Matthews et al, 2008a). One benefit of this type of evaluation is that it can provide evidence that the system is engaging and is suitable for clinical use.…”
Section: Evaluate With Peer Usersmentioning
confidence: 99%
“…A scoping review by Seko et al (2014) suggested that mood-monitoring apps are positively perceived by youth (Matthews et al 2008a), may improve treatment adherence (Matthews et al 2008b) and possibly improve mental wellbeing . While intriguing, findings were preliminary due to the low quality of available evidence (NCCMH, 2014), the small number of studies on mood-monitoring apps specifically and the limited number of apps studied (n = 2) (NCCMH, 2014;Seko et al 2014).…”
Section: Introductionmentioning
confidence: 99%